2006
DOI: 10.1051/animres:2006024
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mating and paternity determinations in domestic swine (Sus scrofa)

Abstract: -When a sow copulates with different boars, fecundation can take a slant towards the best quality male, which should have a more competitive ejaculation. In polyandric animals, genitals can be more elaborated and be an indication of spermatic competence or cryptic female choice. In swine, the male and female genital morphologic characteristics are evidence that allow the assumption of spermatic competence and cryptic choice in this species. In order to prove this hypothesis, the paternity of a group of 18 York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Mate guarding has been reported to play a significant role in sexual selection in wild boar (Delgado et al, 2008). By contrast with previous reports (Aguilera-Reyes et al, 2006), our data were obtained without copulatory restrictions and, particularly in the case of the full sibs forming the analysed group A, no differences in hybrid vigour. Our results clearly show that (a) multiple paternities are possible in domestic pigs under natural mating and (b) when no differences in animal size, development, hybrid vigour or probabilities of mating exist, no differences in paternity success are to be expected.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Mate guarding has been reported to play a significant role in sexual selection in wild boar (Delgado et al, 2008). By contrast with previous reports (Aguilera-Reyes et al, 2006), our data were obtained without copulatory restrictions and, particularly in the case of the full sibs forming the analysed group A, no differences in hybrid vigour. Our results clearly show that (a) multiple paternities are possible in domestic pigs under natural mating and (b) when no differences in animal size, development, hybrid vigour or probabilities of mating exist, no differences in paternity success are to be expected.…”
Section: Resultscontrasting
confidence: 99%
“…Our results can also be useful to further understand the mating system of the wild boar (Costa et al, 2012). There is extensive evidence of multiply sired litters in wild board that are likely to be due to ethological rather than to biological factors (Aguilera-Reyes et al, 2006;Delgado et al, 2008;Poteaux et al, 2009).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Natural migratory events as well as intentional wild boar translocation and restocking of forestlands where this species became extinct 27 28 may have counteracted the effects of factors that tend to reduce population size. Indeed, wild boars can travel considerable distances (sometimes >250 km), particularly when males reach sexual maturity or before the beginning of the mating season 20 , and multiple paternities in a single litter may occur 29 30 . The occasional admixture between pigs and wild boars, could have also augmented the diversity of the latter, since the main porcine commercial breeds carry Asian alleles to a significant extent 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Rearing of piglets is likely cooperative in this species (Kaminski et al , 2005), making misidentification between offspring and their putative mother a distinct possibility. However, in domestic pigs, it has been observed that sows mate with different males and often produce litters of mixed paternity (Aguilera‐Reyes et al , 2006; Drake, Fraser & Weary, 2008). Multiple paternities were also observed in a large proportion of feral sows from another Australian population (Spencer et al , 2005).…”
Section: Discussionmentioning
confidence: 99%